Identifikasi daging babi pada produk olahan dengan polymerase chain reaction-fragmnet length polymorphism (PCR-RFLP) - ABIDIN, Mohammad Zainal ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Identification of the origin of meat used in processed meat products has always been a concern for a variety of reasons including wholesomeness, adulteration, religious factors, and control of unfair-market competition in the meat industry. Hence, preventive fraudulence (falsification) has been always been a vital part to check a food product regulation. The issue to mixed pork in food product is an especially crucial of Halal authentication, of food product. The availability of sensitive and accurate method is essential for monitoring in food product regulation. This research was aimed to detect pork existence at level of 1%. The polymerase chain reaction (PCR) method was assessed with respect to sensitivity and specifity for identification of the origin of meat used in processed meat products. A polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) method had been developed for the identifying pork in mixture to process product including boiling, autoclaving, roasting, frying and detecting of pork in fresh mixture beef, goat meats and chicken meats at level of 1% . The primers L14841 and H15149 were designed in the mitochondrial cytochrome b (cyt b) gene and to produce of amplified fragment was 359 bp. To distinguish between the species of pork from third the meat above, the amplified PCR products were cut with restriction enzyme BseDI fragment 131 and 228 bp. The cyt b PCR-RFLP species identification assay yielded excellent results to know pork existence. This method could be done continuously for detection of pork from other meats for Halal authentication a meat or food.